Development Strategy For a Sustainable Palm Sugar Cooperative Business Model in Sukabumi Regency - Yusri, Amrizal; Sarma, Ma'mun; Raharja, Sapta (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: The Binekas Cooperative, a palm sugar producer cooperative in the Sukabumi Regency, faces an increasing demand for sustainable products that require enhanced economic, environmental, and social performance.Purpose: This study aims to identify cooperative and smallholder profiles, existing business models, and internal and external factors, and formulate strategies for developing a sustainable cooperative business model.Design/methodology/approach: Data were collected through interviews, questionnaires, and literature reviews, from May to August 2024. Analytical methods include situational analysis, Circular Business Model Canvas (CBMC), SOAR analysis (Strengths, Opportunities, Aspirations, and Results), IFAS-EFAS, and Analytic Hierarchy Process (AHP).Findings/Result: The study found that the Binekas Cooperative has a simple organizational structure with strong community roots. Internal and external factors were mapped using CBMC and SOAR to generate four strategic options: expansion of capital access, green productivity optimization, business process standardization, and product diversification through digitalization. Using AHP, the top strategic priority identified was expanding access to capital through inclusive partnerships with member farmers.Conclusion: The cooperative's priority strategy is to expand capital access by strengthening inclusive partnerships with smallholders, who play a key role in governance, and developing a strong, dynamic organizational structure.Originality/value (State of the art): This study shows that the CBMC framework can encourage cooperatives to be adaptive by involving stakeholders under sustainability principles, strengthening governance, enhancing economic activities through social capital within communities, and promoting environmentally friendly production processes. Keywords: AHP, CBMC, Cooperative, Palm Sugar, SOAR